Finite element analysis of cam and its follower contact stress mechanism - Mohd Hafiz, Ghazalli (2007)
Camshaft can be defined as a machine element having the curve outlined or a curved grooved, gives the predetermined specified motion to another element called the follower. In automotive field, Camshaft and its follower take importance roles to run the engine. Nowadays the car maker have developed the vary schemes of cam profile to match with the engine performance. Since the system deals with high load and high speed and many analyses have been carried out on the failure of the components. The analysis is done either by experimental or finite element analysis. The result from the finite element analysis is an approximate of the component failure. In the mean time, the software development is improving in this few decades. Problems with the components such as cam and rocker arm are wears while the valve bends. This project aim determines the stress concentration on the cam and followers during normal operation. More over, this project used the cam, rocker arms, valve lifter, exhaust valve and accessories used in 4G13 engine in type. Solidworks, Cosmosmotion and Algor software are used for determination of stress concentration on the components. The finite element analysis are done for determination of stress concentration during 30 degree of cam where the roller fully climbing the cam and during maximum exhaust valve lift. Cam is rotated at 2000 rpm, 3000 rpm and 6000 rpm of crank rotation. In the analysis, the typical values for coefficient of friction, materials, and spring rate are used. The result from finite element analysis showed that the maximum stress concentration occurred at rocker arm that leads to the failure of the component. Value for maximum stress is over the allowable stress for rocker arm material. Other components are approximately safe where the maximum stress is not over the allowable stress for components.